Post-partum reproductive appearance of buffalo at various levels of GnRH and synchronized with PGF - Yendraliza .; B.P Zespin; Z Udin; Jaswandi . (Jurnal Ilmu Ternak dan Veteriner, 2012)
A study of reproductive performance of buffalo treated with levels of GnRH was conducted on twenty buffaloes of Kampar. The animals were divided into five groups. Group 1 received 200 µg GnRH, the second group received 250 µg GnRH, the third group received 300 µg GnRH, the fourth group received 350 µg GnRH and the fifth group received 400 µg GnRH. Each group also received 12.5 µg PGF2α at days 7 following GnRH injection. Sign of estrus was observed 9 days after GnRH injection. Statistical analysis was performed based on completely randomized design. Results showed that the injection of 300µg of GnRH that was followed by 12,5 µg of PGF2α was able to show obvious sign of post-partum oestrus, with sign of estrus appeared at oestrus rate of 27.8 hours, following PGF2α injection, with 100% of pregnancy rate and 100% of calving rate. Key Words: Estrus, Pregnancy Rate, Calving Rate